Economic sociology of work - Bandelj, Nina (Research in the sociology of work ;, 2009)
The objective of this volume is to apply the economic sociology perspective to issues of work broadly defined. Economic sociology is a vibrant area of research investigating how social structures, power allocations and cultural understandings shape the production, consumption, distribution and exchange of goods and services. The volume consists of three parts. Contributors of this title include prominent senior scholars and promising junior researchers from some of the most eminent academic institutions like Princeton University, Duke University, Brown University, the University of California-Berkeley, and Ecole Normale Superieur, Paris, France.